Association of CCR5 G59029A and RANTES –28 C/G polymorphisms in patients with chronic periodontitis and/or Type 2 Diabetes Mellitus, in a Southeastern Mexican population - Martínez-Aguilar, Victor Manuel; Carrillo-Ávila, Bertha Arelly; García-Escalante, Guadalupe; Vera-Gamboa, Ligia; Escobar-García, Diana María; Pozos-Guillén, Amaury; Guzmán-Marin, Eugenia; Valadez-González, Nina (Investigación Clínica, 2018)
The aim of this study was to determine the association of poly- morphisms CCR5G59029A and RANTES –28C/G in chronic periodontitis (CP) and type 2 diabetes mellitus (T2D). A case control study was carried out that included 163 patients with CP and/or T2D. A periodontal examination was done on all potential participants in order to diagnose CP. To confirm the diag- nosis of T2D, peripheral blood samples were collected for laboratory analyses (blood glucose and glycosylated hemoglobin). Genotyping was performed by PCR-RFLP. The Genotype AA of CCR5 G59029A increased the risk for CP 7.36 times (95% CI = 1.14–78.27, p = 0.03). This genotype’s A allele also increased T2D risk 2.23 times (95% CI = 1.10–4.54, p = 0.02). Genotype CG of RANTES –28 C/G increased CP risk 5.99 times (95% CI = 1.93–18.57, p = 0.002). Its G allele also raised CP risk 4.55 times (95% CI = 1.58–13.04, p = 0.002). In patients suffering both CP and T2D, the CG genotype was associated with the diseases, increasing their risk 4.68-fold (95% CI = 1.60–14.03, p = 0.004). Its  G allele raised CP and T2D risk 3.8 times (95% CI = 1.35–10.67, p = 0.008). The AA genotype and allele A of G59029A polymorphism of CCR5 gene is a risk factor for CP. The CG genotype and allele G polymorphism RANTES –28 C/G gene are risk factors for CP in the population studied. The CG genotype and G allele polymorphism RANTES –28 C/G showed a strong association and a subse- quent risk factor for the coexistence of CP and T2D